Analisis Pola Distribusi Ruruhi (Syzygium polycephalum Merr.) Menggunakan Sistem Informasi Geografis di Kebun Raya Universitas Halu Oleo, Sulawesi Tenggara - Dewi, Wa Ode Nanang Trisna; Erif, La Ode Muhammad; Amrin, Muhammad; Sani, Muhamad Bilal; Rudia, La Ode Adi Parman (MAKILA, 2025)
The Ruruhi plant (Syzygium polycephalum Merr.) is a native species in the Botanical Garden of Halu Oleo University (UHO). This plant supports biodiversity by providing habitat and food sources, enhancing soil quality, and preventing erosion. However, its spatial distribution has not yet been systematically mapped. Due to its ecological and economic value for local communities and the limited information available regarding its distribution and abundance, the Ruruhi plant was selected as the subject of this study. The research aims to obtain detailed information on the distribution patterns of Ruruhi within the UHO Botanical Garden using a Geographic Information System (GIS) approach. The study was conducted through digital mapping utilizing high-resolution Google Earth satellite imagery, followed by field surveys to validate the accuracy of the spatial data. The findings indicate that Ruruhi grows in clusters in areas with high soil moisture and sufficient canopy cover. The Morisita index analysis confirmed a clustered distribution pattern across various growth stages, from seedlings to mature plants, suggesting a strong preference for specific environmental conditions. Furthermore, environmental factors such as temperature, air humidity, soil pH, and soil moisture significantly influenced its distribution. The distribution map from this analysis is expected to serve as a foundational tool for botanical garden management in developing effective conservation strategies, including designing educational trails that enable visitors to observe Ruruhi plants without disturbing their natural habitat. This research contributes to biodiversity conservation efforts and enhances the database of local endemic plant species in the UHO Botanical Garden